An Analysis of Prospective Teacher’s Learning Independence Based on Gender Through the Utilization of Moodle-Based E-Learning - Hermansyah Hermansyah; Nurhairunnisah Nurhairunnisah; Indah Dwi Lestari (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Face to face meeting is not always effective in learning because there are some situations during which it cannot be conducted, such as during the pandemic that we have felt together for these 2 years and even now. Therefore, we need to work around this by learning online through the use of Moodle-based e-learning. This research was conducted at the Faculty of Teacher Training and Education (FKIP) Samawa University with the aim of knowing how gender influences the learning independence of prospective teachers through the use of Moodle-based e-learning. The research sample amounted to 42 students who were divided into 21 males and 21 females. The research data was obtained by distributing a learning independence questionnaire containing 20 statement items that have been adjusted to the indicators of learning independence and calculated using a Likert scale of 1 to 5. The results showed that the significance level value was 0.37, which was greater than 0.05. Therefore, it can be concluded that gender does not affect the learning independence of prospective teacher through the use of Moodle-based e-learning.